An investigation towards a conjugate vaccine against Streptococcus pneumoniae serotype 19A - Trimmel, Astrid Joan (Department of Chemistry, 2018)
Streptococcus pneumoniae is a human pathogen that causes invasive pneumococcal diseases (IPD) such as pneumonia, otitis media and sepsis particularly in children, the elderly, and patients with HIV, and other immunosuppressive conditions. Conjugate vaccines comprised of the bacterial surface polysaccharide conjugated to a carrier protein are very effective in protecting young children against disease by inducing immunological memory and reducing carriage of the bacteria. A pneumococcal conjugate vaccine against seven serotypes (PCV7) was licensed in 2000, which resulted in a dramatic reduction of IPD. However; there was a gradual increase in the number of cases due to non-vaccine serotypes (serotype replacement). Serotype 19A, not included in PCV7 as the structurally similar serotype 19F was assumed to crossprotect against 19A disease, emerged as the most prevalent serotype in several studies with significant presence in Sub-Saharan Africa and South-East Asia and is associated with multidrug resistance. As a result a 13-valent conjugate vaccine that includes serotype 19A was developed and licensed which provided broader coverage. The aim of the work presented in this thesis was to develop processes for the manufacture of 19A capsular polysaccharide (CPS) for the production of a conjugate vaccine based on work performed on the model Pn1. The cultivation process included clonal selection for the growth and isolation of a serotype 19A clone producing high levels of CPS and cultivation using disposable bag technology as an alternative to the traditional fermentor. The culture was inactivated at low temperatures using cold phenol to prevent CPS degradation and to improve the release of CPS from the bacteria. The culture was clarified using a scalable flow-through centrifugation process. The Pn19A polysaccharide was purified using a single step process utilizing differential filtration with ethanol. Analytical tests including identity, purity (from nucleic acid and protein) and size analysis were optimized and performed on Pn19A CPS lots. All purified batches of polysaccharide met World Health Organisation (WHO) specifications as defined in the Technical Report Series. Structural studies were performed on closely related CPS namely; 19F and 19A CPS, both of which contain a labile phosphodiester linkage. The composition of the polysaccharides determined by colorimetric assays was confirmed by hydrolysis and monomeric analysis using gas chromatography/mass spectroscopy (GC/MS) of the methyl glycoside derivatives. Use of 1H, 13C and 31P nuclear magnetic resonance (NMR) experiments confirmed the structure of the 19F and 19A CPS repeating units and permitted determination of the extent of the cell wall polysaccharide contamination. CPS was size-reduced by microfluidization prior to conjugation experiments using cyanylating chemistry and a model carrier protein bovine serum albumin (BSA) and tetanus toxoid (TT). Pn19F and Pn19A conjugates prepared using TT were subjected to thermal stability studies and demonstrated similar stability based on the free saccharide generated. This proof of concept study established small-scale processes that can be further optimized for the manufacture of a conjugate vaccine against Pn19A disease.